Gain improvement of dual-band circular monopole antenna for 2.45/5.5 GHz WLAN applications - Lamultree, Suthasinee; Jansri, Chalee; Phongcharoenpanich, Chuwong (My University, 2019)
This paper presents a gain improvement of dual-band antenna for 2.45/5.5 GHz WLAN applications. The radiating element of the proposed antenna consists of a circular disc monopole with circular-slot laid on FR-4 substrate and backed by a partial ground plane. This partial ground plane is modified to improve its radiation performance. This proposed antenna operates over the frequencies of 2.4-2.485 GHz and 5.15-5.825 GHz with nice radiation characteristics and magnitude of S11 better than -10 dB. An EM simulator has been used in the design and simulation. In addition, an experimental validation was set and measured to compare with the simulated results. All numerical results will be reported and discussed in the paper.
Keywords: Circular monopole antenna; Dual-band antenna; Gain improvement; WLAN applications